Cytokine Levels and Symptoms Among Women with Irritable Bowel Syndrome: Considering the Role of Hormonal Contraceptive Use. Issue 2 (April 2021) - Kamp, Kendra J.; Han, Claire; Shulman, Robert J.; Cain, Kevin C.; Barney, Pamela; Opp, Mark R.; Chang, Lin; Burr, Robert L.; Heitkemper, Margaret M.
Background: Young to middle-aged women are more likely than men to be diagnosed with irritable bowel syndrome (IBS). Immune dysfunction may be present in IBS, however, few studies have tested whether hormonal contraceptive use is linked to inflammatory markers. The purpose of this study was to compare cytokine levels between women (ages 18–45) with and without IBS and with and without hormonal contraceptive use and to examine the relationships of cytokine levels to IBS gastrointestinal (GI) and non-GI symptoms within those using and not using hormonal contraceptives. Methods: Seventy-three women with IBS and 47 healthy control women completed questionnaires (demographics, hormonal contraceptive use) and kept a 28-day symptom diary. Fasting plasma and LPS-stimulated pro-inflammatory (IL-1β, IL-6, IL-12p40, IL-12p70, IL-8, and TNF-α) and anti-inflammatory (IL-10) cytokines were assayed. Results: No differences were found in plasma or stimulated cytokine levels between IBS and control women. Levels of IL-1β ( p = 0.04) and TNF-α ( p = 0.02) were higher among women who did not use hormonal contraceptives compared to women who used hormonal contraceptives. Among women with IBS, significant correlations were found between daily psychological distress and plasma IL-10, IL-12p70, IL-1β, IL-6, and IL-8 cytokine levels. Conclusions: These results suggest that hormonal contraceptive use might reduce IL-1β and TNF-α cytokine levels in women with IBS. The impact of hormonal contraceptive use on innate immune activation among women with IBS requires further research.